O processo de reclamação dos sapais da Ria de Alvor (Portimão) - Almeida, Dina (2014)
Saltmarshes are one of the coastal ecosystems that have endured higher anthropogenic pressures and consequent transformations over the centuries. Its privileged position in transition areas between land and sea (estuaries) has placed these ecosystems at the run for urban-industrial growth and agricultural development. Thus, Ria de Alvor saltmarshes were no exception regarding land use changes, which were mainly driven through the works undertaken by the Development Plans (1940-60). These incorporated saltmarshes´ reclamation for agriculture by exsiccation and the destruction of vegetation, and also building a small wall to prevent salt water to enter (dykedland), leading to the disappearance of about 60% of the Ria de Alvor saltmarshes between 1958 and 2010. However, this process provided the opportunity to new types of marshland to emerge, resulting from the implementation failure of the agricultural dykedland in the Ria de Alvor mouth. The controlled and secondary saltmarshes developed as new typologies of this ecosystem that deserve special attention with regard to habitat management, since they can be differentiated from natural marshes by their structure and floristic composition